Extracts from Pera glabrata (Schott) and Pera distichophylla with anti parasite and antiviral activity - Rodríguez Ortega, Morella; Luna, Diana; Canónico, Yeilis; Carvajal, Zaida; Méndez, Jeannette; Briceño, Luis (Ciencia)
The limited availability of effective and low toxic drugs against diseases such as the South American Tripanosomiasis (Chagas disease) and diseases caused by dengue and yellow fever viruses have encouraged the research for new products on plant extracts. This study presents evidences of the biological effect of extracts from Pera glabrata (Schott) (Pg) and Pera disticophyllia (Pg) when inhibiting both Trypanosoma cruzi (T. cruzi), and viruses (dengue and yellow fever) replications. Pg and Pd (1.56-50 µg/mL) reduced epimastigote form of T cruzireplication from 40% to 100% when the growth was monitored by turbidiometry at 545nm. Vero cells were infected and incubated with extracts (50 and 25 µg/mL). Four days later, cells were stained with Wright-Giemsa and the number of amastigotes was calculated. Only Pg showed a strong inhibition of amastigote replication (90.8%). The antiviral activity of these compounds was determined by lithic plaque reduction. In the case of dengue virus, Pg ethanolic (80%) and aqueous (63%) extracts inhibited the virus replication while Pd inhibited it 100%, the same results were obtained with Pg (25 µg/mL) ethanolic extract on yellow fever replication Our data show that extracts from Pg and Pd are able to inhibit T cruzi, dengue and yellow virus replications.